Literary Field and the Question of Method – Revisited - Gajdosova, Jaroslava (Qualitative Sociology Review, 2008)
Field theory is one of the most efficient and influential analytical schemes in the critical sociology of Pierre Bourdieu, which he consistently developed in his model of literary field. The analytical reliability of the model derives from the way in which Bourdieu combines the structural category of “field” with the phenomenological categories of “doxa” and “habitus”. This article argues that Bourdieu’s selective application of the two phenomenological categories produces a static structural model of literary field where all processes are explained in causal and deterministic terms. The article further seeks to present an alternative reading of the same categories within a discursive model where the processes in literary field and the motivations of its agents are driven by field’s discourses rather than by its rigid structures.